IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI LAHAN TIDUR DI DESA TOMBASIAN ATAS SATU KECAMATAN KAWANGKOAN BARAT (Identification of Factors Affecting the Idle Land in â€œTombasian Atas Satuâ€ Village, West Kawangkoan District) - Lilianinsi Mamoto; Juliana R. Mandei; Olfie Benu (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
Idle land is an area that has agricultural potential but is left without any exploitation efforts on the land. The increase in idle land means that there were inefficiencies in land use, which should be able to produce agricultural products but instead become unproductive. This problem can have an impact on the social and economic aspects of society. â€œTombasian Atas Satuâ€ village was one of the villages that had experienced the phenomenon of increasing idle land.The aim to be achieved in this research was to find out what factors that influenced the increase in idle land in Tombasian Atas Satu Village. The population in this study were 52 idle land owners and all of them were taken as respondents (saturated sampling method). The data analysis method used was the descriptive quantitative one.The results showed that social and economic factors had an effect on the increase in idle land in Tombasian Atas Satu Village. Two of Social factors, namely lifestyle and government support, falled into the high level of influence category, while two others which were the behavior patterns of community relations and land distribution falled in the category of sufficient level of influence. Economic factors including capital, access to raw materials and equipment, product position in the market, and profit margins falled into the high influence category.Land owners should pay more serious attention to their idle land by starting to look for alternative land management such as planting commodities that do not require special treatment such as fruit trees or wood trees.